Exploring students' understanding based on Bruner's theory regarding the concept of profit and loss - Murtafiah, Wasilatul; Rahayu, Maya Puji Lestari; Gembong, Sardulo; Sari, Dwi Rosita; Yahya, Faridah Hanim (Jurnal Elemen, 2024)
The lack of understanding and skills in solving mathematical problems is now a significant concern in many countries. Other factors, such as learning interests, influence students' understanding of these concepts. Therefore, it is necessary to explore students' understanding of arithmetic (profit and loss) based on Bruner's theory regarding learning interest. The study was conducted at a Vocational School in East Java, Indonesia, with 26 students participating as research subjects. The research methodology used was qualitative, with data collected through questionnaires on learning interests, profit and loss concept tests, and interviews. Data were analyzed using a process of reduction, presentation, and conclusions. The findings revealed that subjects with high and medium learning interest categories can meet the stages of Bruner's theory (enactive, iconic, and symbolic). However, subjects with medium learning interests do not need help understanding what happens in the problem—the subject with low learning interest can only reach iconic and symbolic stages in Bruner's theory. Thus, teachers should design appropriate learning strategies and media for students with medium and low learning interests so that they have a good conceptual understanding.